On the vertical wavelength estimates using the Krassovsky parameters of OH airglow monitoring - Ghodpage, R.N.; Taori, A.; Patil, P.T.; Siingh, Devendraa; Gurubaran, S.; Sharma, A.K. (My University, 2015)
The photometric measurements of mesospheric OH and O(¹S) emission, carried out from Kolhapur (16.8°N, 74.2°E), Maharashtra during January-April 2005 are used to study the wave characteristics. The nocturnal variability reveals the dominant long-period wave signatures with significant amplitudes of embedded short-period waves. We carry out a sensitivity study on the vertical wavelength (VW) derived with the help of Krassovsky parameters (η = |η|eiφ) of the OH data, which reveals VW to vary from 38.9 to 110.2 km. This was compared with the VW estimates using the phase difference of the simultaneously observed waves in both OH and O(¹S) emission intensities. Results reveal that in the absence of attitudinally resolved measurements, the VW estimated using Krassovsky method can be used.
Keywords: Photometric measurements; Mesospheric; Krassovsky; Airglow